Biofilm formation by prototheca zopfii isolated from clinical and subclinical bovine mastitis in distinct growth conditions under different dyes - Ely, Valessa Lunkes; Gressler, Letícia Trevisan; Sutili, Fernando Jonas; Ribeiro, Márcio Garcia [UNESP]; da Costa, Mateus Matiuzzi; de Vargas, Agueda Castagna; Botton, Sônia de Avila (FapUNIFESP (SciELO), 2019)
Prototheca spp. have been reported as an emergent environmental mastitis pathogen in several countries. Biofilm formation is a significant factor associated with different degrees of virulence developed by many microorganisms, including Prototheca spp. The present study aimed to compare two growth conditions and two staining dyes to determine which combination was more appropriate to evaluate qualitatively and quantitatively the production of biofilm by P. zopfii. Biofilm formation was evaluated in polystyrene microplates under static and dynamic growth conditions and staining with crystal violet or cotton blue dye. All P. zopfii isolates from cows with mastitis were classified as biofilm-producers in all growth conditions and staining. The cotton blue dye proved to be more appropriate method to classify the intensity of P. zopfii biofilm production.
Formação de biofilme por prototheca zopfii isolados de mastite bovina clínica e subclínica em distintas condições de crescimento sob diferentes corantes
Keywords: Bovine mastitis; Dairy cattle; Intramammary infections; Microplate biofilm assay; Prototheca zopfii; Virulence factor